Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-main.401
|View full text |Cite
|
Sign up to set email alerts
|

DirectProbe: Studying Representations without Classifiers

Abstract: Understanding how linguistic structure is encoded in contextualized embedding could help explain their impressive performance across NLP. Existing approaches for probing them usually call for training classifiers and use the accuracy, mutual information, or complexity as a proxy for the representation's goodness. In this work, we argue that doing so can be unreliable because different representations may need different classifiers. We develop a heuristic, DIRECTPROBE, that directly studies the geometry of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Note that there are also many probing papers without post-hoc classifiers (Zhou and Srikumar, 2021;Torroba Hennigen et al, 2020;Li et al, 2021). While many of these do not mention the term "probing", they nevertheless probe the intrinsics of deep neural models.…”
Section: Probing Methodsmentioning
confidence: 99%
“…Note that there are also many probing papers without post-hoc classifiers (Zhou and Srikumar, 2021;Torroba Hennigen et al, 2020;Li et al, 2021). While many of these do not mention the term "probing", they nevertheless probe the intrinsics of deep neural models.…”
Section: Probing Methodsmentioning
confidence: 99%
“…In this work, we will probe representations in the BERT family at various points during and after fine-tuning. As a first step, let us look at the two supervised probes we will employ: a classifier-based probe to assess how well a representation supports classifiers for different tasks, and DIRECTPROBE (Zhou and Srikumar, 2021) to analyze the geometry of the representation.…”
Section: Preliminaries: Probing Methodsmentioning
confidence: 99%
“…There are also efforts to inspect the representations from a geometric persepctive (e.g. Ethayarajh, 2019;Mimno and Thompson, 2017), including the recently proposed DIRECTPROBE (Zhou and Srikumar, 2021), which we use in this work. Another line of probing work is to design control tasks (Ravichander et al, 2021;Lan et al, 2020) to reverse-engineer the internal mechanisms of representations (Kovaleva et al, 2019;.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have focused on the remarkable potential of pre-trained language models, such as BERT (Devlin et al, 2019), in capturing linguistic knowledge. They have shown that pretrained representations are able to encode various linguistic properties (Tenney et al, 2019a;Talmor et al, 2020;Goodwin et al, 2020;Wu et al, 2020;Zhou and Srikumar, 2021;Chen et al, 2021;Tenney et al, 2019b), among others, syntactic, such as part of speech (Liu et al, 2019a) and dependency tree (Hewitt and Manning, 2019), and semantic, such as word senses (Reif et al, 2019) and semantic dependency (Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%